2013
DOI: 10.1371/journal.pone.0065004
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling Responses to Mountain Pine Beetle Disturbance in a High Elevation Whitebark Pine Ecosystem

Abstract: Ecological disturbances can significantly affect biogeochemical cycles in terrestrial ecosystems, but the biogeochemical consequences of the extensive mountain pine beetle outbreak in high elevation whitebark pine (WbP) (Pinus albicaulis) ecosystems of western North America have not been previously investigated. Mountain pine beetle attack has driven widespread WbP mortality, which could drive shifts in both the pools and fluxes of nitrogen (N) within these ecosystems. Because N availability can limit forest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
4
12
1
Order By: Relevance
“…In contrast to the burned plots, there is no change in pH in MPB plots ( Figure A3), which is consistent with several previous studies [32,36,91,92]. Unlike fire, which increases soil pH and potential for rapid leaching of soluble organic material, beetle-induced tree mortality reduces C and nutrient inputs to the soil from root exudates and litterfall in the short term, which is followed by increased C inputs from leaf, branch and root litter necromass [31,32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to the burned plots, there is no change in pH in MPB plots ( Figure A3), which is consistent with several previous studies [32,36,91,92]. Unlike fire, which increases soil pH and potential for rapid leaching of soluble organic material, beetle-induced tree mortality reduces C and nutrient inputs to the soil from root exudates and litterfall in the short term, which is followed by increased C inputs from leaf, branch and root litter necromass [31,32].…”
Section: Discussionsupporting
confidence: 90%
“…Our study suggests that the environmental factors limiting microbial function shift depending on whether fire or pathogeninduced mortality is the disturbance agent. Our results are consistent with studies limited to single disturbances [31,32,40,50,92,94]. Soil biogeochemical processes can be represented through a variety of modeling approaches including a simple bulk substrate, moisture and Q10 response [105], a more complex treatment of soil substrate suitability [62,106], or even trait-based approaches [107,108].…”
Section: Discussionsupporting
confidence: 88%
“…Given reported changes in soil chemistry following bark beetle infestations ( Morehouse et al, 2008 ; Clow et al, 2011 ; Xiong et al, 2011 ; Griffin and Turner, 2012 ; Keville et al, 2013 ), bark beetle-induced tree mortality might alter the structure of soil bacterial communities via environmental filtering. Alternatively, stronger relative influences of stochastic processes in the assembly of soil bacterial communities have been noted following disturbance ( Ferrenberg et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Clow et al (2011) observed no significant changes in stream-water NO 3 or DOC, however, total N and P increased. Interestingly, Griffin et al (2011) and Keville et al (2013) concluded that, although MPB outbreaks significantly altered the N cycling, the net effects were surprisingly minor given the extent of the beetle-caused mortality. Conversely, MPB outbreaks may also influence cation and aluminum fluxes as increased nitrification reduces the soil pH and leads to the exchange and loss of base cations (Ca 2+ , K + , Mg 2+ ); however further studies are required to confirm these changes.…”
Section: Nutrient Cyclingmentioning
confidence: 99%